Meta-analysis of NAD(P)(H) quantification results exhibits variability across mammalian tissues - Azouaoui, Dassine; Choinière, Michael René; Khan, Momtafin; Sayfi, Shahab; Jaffer, Simran; Yousef, Selvia; Patten, David A.; Green, Alexander E.; Menzies, Keir J. (Scientific reports, 2023)
Nicotinamide Adenine Dinucleotide (NAD + ) plays an important role in energy metabolism and signaling pathways controlling crucial cellular functions. The increased interest in NAD + metabolism and NAD + -boosting therapies has reinforced the necessity for accurate NAD + quantification. To examine the published NAD(P)(H) measures across mammalian tissues, we performed a meta-analysis of the existing data. An Ovid MEDLINE database search identified articles with NAD(P)(H) quantification results obtained from mammalian tissues published between 1961 and 2021. We screened 4890 records and extracted quantitative data, as well as the quantification methods, pre-analytical conditions, and subject characteristics. The extracted physiological NAD(P)(H) concentrations in various tissues from mice, rats, and humans, revealed an important inter- and intra-method variability that extended to recent publications. This highlights the relatively poor potential for cross-experimental analyses for NAD(P)(H) quantitative data and the importance of standardization for NAD(P)(H) quantification methods and pre-analytical procedures for future preclinical and clinical studies.